English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Please show work

2007-05-01 06:32:18 · 3 answers · asked by tzc_1 1 in Science & Mathematics Mathematics

3 answers

x^2 + 5x - 6 = 0
(x -6) (x+ 1) = 0
Either x - 6 = 0
x = 6

or x +1 = 0
x = -1

2007-05-01 06:43:59 · answer #1 · answered by Mehn 3 · 0 0

x^2+5x=6
(1/2*(5))^2=25/4
x^2+5x+25/4 = 6+25/4
(x+5/2)^2 = 49/4
x+5/2 = 7/2
x=2/2
x=1

2007-05-01 14:06:42 · answer #2 · answered by Diggity 3 · 0 0

(x + 6).(x - 1) = 0
x = - 6, x = 1

2007-05-01 13:35:39 · answer #3 · answered by Como 7 · 0 0

fedest.com, questions and answers